The perception of learning english by undergraduate students - Mohd Nazri, Latiff Azmi; Ekalestari, S.; Putri, F. (2018)
This research analyzed the perception of undergraduate students on learning English. This research adopted the theory on perception proposed by Efron (1968) in which he stated that perception is the primary cognitive contact of person with the world around him. It was completed by adopting quantitative method in which the data were collected by sharing questionnaire to undergraduate students as its respondents. The questionnaire was tested by Product Moment Pearson to meet its validity with t-table larger than r-table, and by Alpha Coefficient to meet its reliability with Cronbach's Alpha value larger than 0,6. Furthermore, the data obtained from the questionnaire were analyzed by using Likert Scale with four alternative responses. They were Strongly Disagree (0% - 24.99%), Disagree (25% - 49.99%), Agree (50% - 74.99%), and Strongly Agree (75% - 100%). The research found that the perception of the respondents towards English learning is 66%.